How logic works : a user's guide - Halvorson, Hans (Princeton University Press, 2020)
"Logic instruction typically takes two forms. The first has the aim of teaching students to solve a certain sort of problem as efficiently as possible. This is the approach adopted by most logic textbooks and truth trees, the most popular method, gives students an algorithm for solving logic problems. The second has as its aim teaching students a certain style of thinking and, thus, concerns itself with how students solve problems. In How Logic Works, Hans Halvorson introduces students to the methods of natural deduction, a method which not only helps them solve problems, but helps them to understand the principles of valid reasoning for themselves. Halvorson uses formal logic to train students in the task of constructing paths between premises and conclusions. The student, then, will become an expert traveller in logical space, quickly recognizing the difference between a safe path (where truth is guaranteed to be preserved) and a hazardous path (where truth might be lost). This approach is premised on the fact that if a student learns natural deduction, she learns a skill that transfers to any domain where valid deductive reasoning is useful"--